2017
DOI: 10.18502/sjms.v12i2.920
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus_Surface Gene Mutations and Their Clinical Implications

Abstract: Hepatitis B infection is a major public health problem caused by hepatitis B virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These mutations played a significant role in the virus immune escape, and these variations have largely been justified by factors associated with host immunity, such as HBV-specific T-and/or B-cell production, and antigen presentation failure. Additionally, viral determinants, such as the HBV genotypes and their evolving variants, have played a significant role in contributing to these variations [39,40]. A study reported that surface antigen causes dysfunction of myeloid dendritic cells, which serve as a possible immune escape mechanism in HBV [39].…”
Section: Discussionmentioning
confidence: 99%
“…These mutations played a significant role in the virus immune escape, and these variations have largely been justified by factors associated with host immunity, such as HBV-specific T-and/or B-cell production, and antigen presentation failure. Additionally, viral determinants, such as the HBV genotypes and their evolving variants, have played a significant role in contributing to these variations [39,40]. A study reported that surface antigen causes dysfunction of myeloid dendritic cells, which serve as a possible immune escape mechanism in HBV [39].…”
Section: Discussionmentioning
confidence: 99%
“…HBV vaccine is a recombinant DNA vaccine that contains HBsAg genetically engineered from the yeast Saccharomyces cerevisiae. It provides a seroprotection rate of 85-100% that was seen one month after the last dose of vaccine and it confers immunity for at least 10 years [5]. Hepatitis B vaccine is recommended for unvaccinated adults who are at risk for HBV infection like people whose sex partners have hepatitis B, sexually active persons who are not in a long-term monogamous relationship, persons seeking evaluation or treatment for a sexually transmitted disease, men who have sex with men, people who share needles, syringes, or other drug-injection equipment, household contacts of HBV-infected persons, health personnel and public safety workers at risk for exposure to blood or body fluids, residents and staff of facilities for developmentally disabled persons, persons in correctional facilities, victims of sexual assault or abuse, travelers to regions with increased rates of hepatitis B, people with chronic liver disease, patients on hemodialysis, HIV infection, or diabetes, and anyone who wants to be protected from HBV.…”
Section: Introductionmentioning
confidence: 99%